Fashion E-Commerce Website Design Using the Waterfall Method - Roynaldy Rosdiyanto; Deny Novianti; Siti Fatimatul Zuhro (bit-Tech, 2026)
The rapid development of information and communication technology has significantly influenced various sectors, including the trade industry. One sector experiencing notable growth is the fashion industry. The increasing use of the internet and digital devices has changed consumer behavior, with many people preferring online shopping for its convenience, efficiency, and accessibility. This trend has encouraged fashion businesses to adopt digital platforms such as e-commerce websites to expand their market reach and improve customer service. This study aims to design and develop a fashion e-commerce website that facilitates online buying and selling transactions. The system is expected to help fashion business owners promote and market their products more effectively while providing consumers with greater convenience in accessing product information and completing purchases. The system's development process uses the waterfall method, comprising the following stages: requirements analysis, system design, implementation, testing, and deployment. This method is chosen because it provides a structured and systematic approach to software development. The results of this study indicate that the fashion e-commerce website was successfully developed, featuring a product catalog, shopping cart, payment system, and order management. System testing was conducted using the black-box testing method, demonstrating that all features function properly in accordance with the specified system requirements. Therefore, the developed website can support digital marketing and enhance the online shopping experience for consumers.